2014
DOI: 10.1021/ja504078b
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Controlled Partition of Carbon Nanotubes in Polymer Aqueous Two-Phase Systems

Abstract: Sorting single-wall carbon nanotubes (SWCNTs) of different chiralities is both scientifically interesting and technologically important. Recent studies have shown that polymer aqueous two-phase extraction is a very effective way to achieve nanotube sorting. However, works published to date have demonstrated only separation of surfactant-dispersed SWCNTs, and the mechanism of chirality-dependent SWCNT partition is not well understood. Here we report a systematic study of spontaneous partition of DNA-wrapped SWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
238
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(243 citation statements)
references
References 29 publications
3
238
1
1
Order By: Relevance
“…Prior to investigating ssDNA desorption from SWCNTs, ssDNA adsorption was investigated to both confirm adsorption and to determine baseline values for characterizing subsequent desorption. (GT) 20 was chosen as the model ssDNA oligomer because it has been used for the chirality‐specific separation of SWCNTs and because we have found that longer ssDNA strands yield a higher concentration of SWCNT in suspension after probe sonication and centrifugation (typical optical density x dilution factor 20–30, see Figure S1 in the Supporting Information) . The photographs of the suspension in Figure (a) shows the produced SWCNT suspension was stable (for months) and recorded a zeta potential of −42 mV, which is similar to other reports of CNT‐DNA suspensions and similar in magnitude to SWCNT suspensions with anionic surfactant sodium deoxycholate (Figure S2) .…”
Section: Resultsmentioning
confidence: 99%
“…Prior to investigating ssDNA desorption from SWCNTs, ssDNA adsorption was investigated to both confirm adsorption and to determine baseline values for characterizing subsequent desorption. (GT) 20 was chosen as the model ssDNA oligomer because it has been used for the chirality‐specific separation of SWCNTs and because we have found that longer ssDNA strands yield a higher concentration of SWCNT in suspension after probe sonication and centrifugation (typical optical density x dilution factor 20–30, see Figure S1 in the Supporting Information) . The photographs of the suspension in Figure (a) shows the produced SWCNT suspension was stable (for months) and recorded a zeta potential of −42 mV, which is similar to other reports of CNT‐DNA suspensions and similar in magnitude to SWCNT suspensions with anionic surfactant sodium deoxycholate (Figure S2) .…”
Section: Resultsmentioning
confidence: 99%
“…The (6,5) SWCNTs separated by ATP methods also have a high purity, but the detailed purity value was not evaluated by authors of Refs. .…”
Section: Resultsmentioning
confidence: 99%
“…Purification of the (9,4) nanotube from the unsorted ssCTTC 3 TTC-SWCNT sample was performed using the aqueous two-phase extraction method 1820 . In brief, ssCTTC 3 TTC-SWCNT was mixed with a solution containing a final concentration of 7.76% polyethylene glycol (PEG, molecular weight 6 kDa, Alfa Aesar), and 15.0% polyacrylamide (PAM, molecular weight 10 kDa, Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%